ENTREPRENEURIAL COACHING FOR THE DEVELOPMENT OF ENTREPRENEURIAL SELF-EFFICACY IN WOMEN ENTREPRENEURS - Molema, Lerato; Hlatshwayo, Elona; Ebewo, Patrick (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study explored entrepreneurial coaching to develop women entrepreneurs by enhancing their entrepreneurial self-efficacy. It sought to understand how entrepreneurial self-efficacy in women entrepreneurs can be developed through entrepreneurial coaching. Design/methodology/approach: This study's methodology was a descriptive literature review.Findings: The findings showed that entrepreneurial coaching is a development intervention that can be used to enhance the entrepreneurial self-efficacy beliefs of women entrepreneurs, thereby increasing their chances of engaging in successful business creation and operation.Research limitations/implications: Entrepreneurial coaching for women entrepreneurs as a research field is still in its developmental stage, as such, there are limited sources of literature. Practical implications: The study contributes to the overall discourse on entrepreneurial coaching as a supportive intervention in enhancing entrepreneurial self-efficacy for women entrepreneurs. Originality/value: The combination of entrepreneurial coaching, entrepreneurial self-efficacy and the development of women entrepreneurs is still emerging.